ANALISIS BENTUK PADA IDENTITAS VISUAL STMIK STIKOM INDONESIA - I Nyoman Jayanegara; i nyoman anom fajaraditya setiawan (LPPM Institut Bisnis dan Teknologi Indonesia, 2020)
Visual identity as a sign system that is used consistently to communicate messages widely. This is very important to be a consideration in building positive branding. The design elements contained in visual identity should be able to be clear and specific in their function as sign systems. In STMIK STIKOM Indonesia as an entity, it has a logo and a symbol as its visual identity. The use of these two things becomes somewhat ambiguous when published to the public and can lead to confusion about the reception of the message. In this visual identity study as a sign system, data will be collected in various fields related to logos and symbols in various media created by institutions. So that the data can be analyzed taxonomically by considering the construction, fields, letters, colors, and forms of placement in various elements. The results of the study found that the inconsistency of the use of visual identity, the use of different colors on the logo or symbol, removal of some parts of the logo, and the destruction of the logo structure with a disproportionately step. The fundamental finding is the emergence of ambiguity in visual identity and the necessity of having standard rules through manual graphic standards as a reference for the use or utilization of agreed visual identity.